2000
DOI: 10.1103/physrevlett.84.3744
|View full text |Cite
|
Sign up to set email alerts
|

Universal Fluctuations in Correlated Systems

Abstract: The probability density function (PDF) of a global measure in a large class of highly correlated systems has been suggested to be of the same functional form. Here, we identify the analytical form of the PDF of one such measure, the order parameter in the low temperature phase of the 2D-XY model. We demonstrate that this function describes the fluctuations of global quantities in other correlated, equilibrium and non-equilibrium systems. These include a coupled rotor model, Ising and percolation models, models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
357
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(391 citation statements)
references
References 16 publications
29
357
1
2
Order By: Relevance
“…Moreover, we can address the question of the generality of the observed non-analyticity of the large deviation function in systems in permanent regime where the velocity field is unbounded: from our analysis of the Langevin system, we think that such anomalies could be widely encountered in dissipative far-from-equilibrium systems. An interesting perspective is besides to consider extremely correlated noises, in order to check in this context the ideas exposed in [15,16], where some conjectures are made on the limiting behaviours of the pdf of global variables in highly correlated systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we can address the question of the generality of the observed non-analyticity of the large deviation function in systems in permanent regime where the velocity field is unbounded: from our analysis of the Langevin system, we think that such anomalies could be widely encountered in dissipative far-from-equilibrium systems. An interesting perspective is besides to consider extremely correlated noises, in order to check in this context the ideas exposed in [15,16], where some conjectures are made on the limiting behaviours of the pdf of global variables in highly correlated systems.…”
Section: Resultsmentioning
confidence: 99%
“…The calculation leading to (16) and (18) assumes a priori λ > 0, but it is useful to study the properties of the analytical continuations of these formulae. First, one remarks that the square root in the definition of η does not induce any breaking of analyticity, for it appears always in quantities such cosh(η γ) or sinh(η γ)/η which are entire functions of λ.…”
Section: Characteristic Functionsmentioning
confidence: 99%
“…It has been observed that very similar distributions occur in two and three dimensional Ising models at a temperature T * (L) slightly below, but close to the critical temperature [14,15]. We have argued that this is a critical phenomenon [14,16], giving weight to our earlier proposition [12] that many correlated systems, both in and out of equilibrium, can be driven into a state with very similar fluctuations [14,17], irrespectively of their universality class.…”
mentioning
confidence: 89%
“…We have argued that this is a critical phenomenon [14,16], giving weight to our earlier proposition [12] that many correlated systems, both in and out of equilibrium, can be driven into a state with very similar fluctuations [14,17], irrespectively of their universality class.…”
mentioning
confidence: 99%
“…[36,[54][55][56][57][58][59][60]. For the original PDES scheme (p=0, regular lattice synchronization) exhibiting a KPZ-like rough (or critical) surface, we illustrated (Sect.…”
Section: Extremal Fluctuations Of the Virtual Time Horizonmentioning
confidence: 99%